Implementasi Media Pembelajaran Berbasis Game Edukasi Math Playground di SMP IV-7 Siliragung Banyuwangi - Fatqurhohman Fatqurhohman; Hairul Huda; Elvira Haryanti Lara Disma; Merlin Cristianda Ayu Lestari (Universitas Muhammadiyah Jember, 2023)
As technology advances in the Industrial Revolution 5.0 era, learning is now required to apply digital-based learning, so that the learning process is more interesting and fun and can be done by anyone, anytime, and anywhere, regardless of age, distance, and place. The main objective of this activity is the implementation of the use of learning media based on the Math Playground Educational Game. This media contains many features, such as Math Games, Logic Games, Math Arcade, Story Math, Math Video. The material contained in it includes Numbers and Algebra, Geometry, Exploration, Problem Solving Games, and other material related to mathematics. This activity was carried out at SMP Kartika IV-7 Siliragung. The results of the activity show that this educational game helps instill mathematical concepts in students, because this application has many material features that can be learned by participants (students) such as learning addition, subtraction, multiplication, division, roots, decimal numbers, to exponential fractions. In addition, the role of educators (teachers) and parents also plays a vital role in accompanying children in learning so that they can use and take advantage of technological advances wisely